P743 Bone mineral disease is insufficiently evaluated in patients with inflammatory bowel disease at risk of metabolic bone disease: results from a Danish population-based inception cohort study. (25th January 2019) - Lo, B; Vind, I; Vester-Andersen, M K; Holm, J P; Bendtsen, F; Burisch, J
Abstract: Background: Patients with inflammatory bowel disease (IBD) including Crohn's disease (CD) and ulcerative colitis (UC) are at risk of developing metabolic bone disease. No general agreement regarding osteoporosis screening by Dual-energy X-ray absorptiometry (DXA) in IBD patients exists. The aims were to investigate the screening strategy, incidence and risk factors of osteoporosis in a well-defined prospective population-based inception cohort. Methods: Between 2003 and 2004 all incident patients diagnosed with CD and UC in a clearly defined Copenhagen area were included and followed until 2015. Data regarding hospitalisation, diagnosis and treatment were collected from patient files and national registries. Data were compared with a control population (1:20). Poisson's regression model was performed for osteoporosis and a combined variable of osteoporosis and osteopenia with several covariates. Results: A total of 513 patients with IBD were included (213 CD, 300 UC). Overall, 297 (58%, CD: 144 [68%], UC: 153 [51%]) patients received ≥2 courses of steroids within a year, resulting in 624 patient-years where 2 or more courses of steroids where given within a year. Of those, only 65 (10.4%) cases of patient-years were followed by DXA within the same or next calendar year. Overall, 50 (9.7%, Table 1) IBD patients (CD: 21 [9.9%], UC: 29 [9.7%]) and 562 (5.5%, p < 0.001) controls were diagnosed with osteoporosis during follow-up (OR: CD: 1.9 [1.2–3.0], UC: 1.8 [1.2–2.7]). Age at diagnosis (IRR, CD: 1.05 [1.02–1.07], UC: 1.06 [1.04–1.10]) was significantly associated with the risk of osteoporosis. When assessing low energy fractures, 6 (2.8%) CD and 10 (3.3%) UC patients had at least one; independent of steroid treatment (p>0.05). No significant difference was found compared with the control population (238 [2.3%], p = 0.5). Assessment of BMD, T- and Z-score found on DXA showed no significant differences between UC and CD patients at any bone site, nor in subgroups of disease phenotypes. Conclusions: In this population-based inception cohort with 10 years of follow-up, 10% of IBD patients were diagnosed with osteoporosis, bone mineral density among patients at risk of osteoporosis receiving steroid treatment was inadequately evaluated. Increased attention to IBD patient at risk of metabolic bone disease must be prioritised and guidelines on this matter are warranted.